Communication and democratic reform in South Africa - Horwitz, Robert Britt (Cambridge ; New York : Cambridge University Press, 2001)
The book examines the reform of the communication sector in South Africa in the transition from apartheid to democracy. It studies the complex political process by which broadcasting, telecommunications, the state information agency, and the print press were transformed from apartheid-aligned apparatuses to accountable democratic institutions.
Tables; Preface and Acknowledgments; Acronyms and Abbreviations; Chapter 1 Introduction and Overview; Chapter 2 The Ancien Régime in the South African Communications Sector; Chapter 3 Sharing Power without Losing ControlŽ: Reform Apartheid and the New Politics of Resistance; Chapter 4 Control Will Not Pass to UsŽ: The Reform Process in Broadcasting; Chapter 5 All Shall CallŽ: The Telecommunications Reform Process; Chapter 6 Free but ResponsibleŽ: The Battle over the Press and the Reform of the South African Communication Service.
Includes bibliographical references (pages 359-393) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Communication policy -- South Africa; Democracy -- South Africa; Communication -- Politique gouvernementale -- Afrique du Sud; LANGUAGE ARTS & DISCIPLINES -- Communication Studies; Communication policy; Democracy; South Africa; Demokratisierung; Kommunikation; Massamedia; Overheidsbeleid; Democratie; Démocratie -- Afrique du Sud; Politique de la communication -- Afrique du Sud; Médias -- Afrique du Sud; Südafrika <Staat>; Communication; Télécommunications.; Radiodiffusion; Apartheid; Démocratie.; Presse; Réformes.; Afrique du Sud; Communication policy -- South Africa; Democracy -- South Africa; Samfundsvidenskab -- Sociologi; Electronic book